Metodologías Participativas en el proceso de enseñanza aprendizaje de Estudios Sociales, sexto grado, Escuela de Educación Básica Municipal Ecológica, período 2024-2025 - Aucapiña Suárez, Astrid Nathali (2025)
Participatory Methodologies are the set of strategies, techniques and methods that allow improving the educational process. The present Curricular Integration Work investigated the use of Participatory Methodologies in the teaching-learning process of Social Studies. Thus, the general objective was to determine the incidence of Participatory Methodologies in the teaching-learning process of Social Studies, Block 1 - History and Identity, in the sixth grade of the Escuela de Educación Básica Municipal Ecológica period 2024-2025. A mixed-approach research was utilized, descriptive type with a non-experimental design, the methods employed were analytical, descriptive, inductive, deductive, synthetic, hermeneutic, interpretive and descriptive statistics. Among the techniques applied were observation, teacher interview and student survey, the instruments: an interview guide for the teacher and a questionnaire for the student, which were carried out based on the specific objectives. The results of the interview indicated that the teacher does not know what participatory methodologies are and how to employ them; for this reason the same didactic with a traditionalist tendency are maintained; according to the answers of the survey, these allowed to know that the educator maintains a positive attitude to address each student and correct an error, however the learners consider that their teacher should change the way of explaining the contents of Social Studies, in view of this; Participatory Methodologies at any educational level, strengthen the intervention of the student in personal learning and in the effort to act in a responsible, participatory, creative and motivated manner in the classroom, all this awakens the student's interest in learning by doing